Fostering Sustainability through Educational and Research Initiatives at ETUT - Gurbanmyrat Mezilov; Lachyn Gurdova; Jeren Kulyyeva; Mahmudova Nurjahan; Atamyrat Altyyev; Dovlet Annamuradov; Yslam Orazov (Journal of Sustainability Perspectives, 2024)
This paper conducts a comparative analysis of sustainability-focused educational initiatives at Oguz Han Engineering and Technology University of Turkmenistan (ETUT) alongside other young universities, including Duke Kunshan University (China), Ashoka University (India), Singapore University of Technology and Design (SUTD), and King Abdullah University of Science and Technology (KAUST, Saudi Arabia). The study examines how these institutions integrate sustainability into their curricula, student engagement, and community outreach efforts, emphasizing the role of emerging universities in advancing sustainability education. Through an in-depth case study of ETUT and a comparative review of global trends, the research highlights innovative approaches aligned with the United Nations Sustainable Development Goals (SDGs). This paper illustrates how young universities leverage their agility to embed sustainability into their operations, curricula, and community interactions, preparing students to address pressing environmental and social challenges in the 21st century.